How I treat febrile neutropenia - Marcio Nucci (Mediterranean Journal of Hematology and Infectious Diseases)
The management of febrile neutropenia is a backbone of the treatment of patients with hematologic malignancies, and has evolved over the past decades. This article reviews my approach to the evaluation and treatment of febrile neutropenic patients. Key topics discussed include antibacterial and antifungal prophylaxis, the initial workup for fever, the choice of the empiric antibiotic regimen and its modifications, and criteria for discontinuation. For each of these questions, I review the literature and present my perspective.